Growth management and prevalence of underweight of indigenous children (Orang Asli) in Peninsular Malaysia: a clinical audit - Chii-Chii CHEW; Hasni-Adha IBRAHIM; Venugopalan K. BALAN; Nor-Aziz; Hooi-Meng PUAH; Amar-Singh HSS (BMC, 2022)
Abstract Background Most indigenous people (Orang Asli in Peninsular Malaysia) live in poverty, and their children are at risk of growth problems due to nutrition deficiency. Routine health and growth assessments are essential to identify these children. This clinical audit aimed to determine the growth management of indigenous children and the prevalence of underweight among these children in Perak state, Malaysia. Methods A clinical audit was conducted in 2016 after obtaining consensus from stakeholders for audit criteria, forms, and procedures. All weight-for-age growth charts of Orang Asli children aged 2 and below were sampled for retrospective audit. This audit excluded children who required special needs. Growth charts were examined against audit criteria: (i) quality of growth chart plotting (charts were not plotted, incompletely plotted, or incorrectly plotted), (ii) presence of underweight, and (iii) appropriateness of action taken (appropriate or inappropriate action) according to local standard operating policies. Eligible auditors were first trained using simulated growth charts. Results Out of 1329 growth charts audited, 797 (60%) growth charts were correctly plotted, 527 (39.7%) were incompletely or incorrectly plotted, and five (0.3%) were not plotted. Overall, 40.0% of the growth chart was plotted incorrectly or completely not plotted. 550 (41.4%) children were found to be underweight, and 71.5% of them received inappropriate care management. Where growth charts were correctly plotted, 283 children were identified with underweight problems, and 194 (68.6%) of them received inappropriate care. For growth charts that were plotted incompletely or incorrectly, 267 children were identified as having underweight problems, and 199 (74.5%) received inappropriate care. The growth status of 265 (19.9%) children was unable to be determined due to incomplete plotting. Conclusion Approximately 40% of indigenous Orang Asli children aged 2 years and under were underweight, and most of them received inappropriate care.